Nondestructive Testing of Linear-Butt Welding with the Phaser XS - Tihanov-Tănăsache, Daniel; Oancă, Octavian Victor; Duma, Iuliana; Florea, Vlad Alexandru (Advanced materials research, 2019)
In certain welded constructions (e g. trails pipes) the weld root is no longer accessible after its completion. As a result, the weld root defects cannot be visually observed. Under these circumstances the root must be examined with ultrasounds on the other accessible side of the seam. The paper .presents the results of the flaw examination which was subject to an pipe, butt welded, made it with coated electrodes